2017
DOI: 10.1136/bcr-2017-221402
|View full text |Cite
|
Sign up to set email alerts
|

RUNX1-RUNX1T1-positive acute myeloid leukaemia presenting as bilateral proptosis and multiple cranial nerve palsy

Abstract: We describe a unique presentation of acute myeloid leukaemia (AML) with myeloid sarcoma (MS), manifested as proptosis with multiple cranial nerve palsies in a 9-year-old boy. MRI of the brain revealed multiple enhancing lesions and bilateral mastoiditis, in addition to sagittal sinus thrombosis. Peripheral blood smear demonstrated blasts showing Auer rods. Bone marrow examination confirmed the diagnosis of AML. PCR was positive for RUNX1-RUNX1T1. Neurological deficits improved with induction chemotherapy for A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Patient underwent AML 15 Medical Research Council protocol and cranial radiotherapy and attained a 1-month disease-free survival at the time of publication of the case report. 18 Additionally, Kondo et al, reported a case of a 7-year-old male with RUNX1::RUNX1T1 translocated AML who achieved complete remission after conventional chemotherapy but relapsed after six (6) months, like in our first case. 19 RUNX1::RUNX1T1 is also used in MRD monitoring through multiparameter-flow cytometry or molecular techniques.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Patient underwent AML 15 Medical Research Council protocol and cranial radiotherapy and attained a 1-month disease-free survival at the time of publication of the case report. 18 Additionally, Kondo et al, reported a case of a 7-year-old male with RUNX1::RUNX1T1 translocated AML who achieved complete remission after conventional chemotherapy but relapsed after six (6) months, like in our first case. 19 RUNX1::RUNX1T1 is also used in MRD monitoring through multiparameter-flow cytometry or molecular techniques.…”
Section: Discussionsupporting
confidence: 62%
“…Totadri et al, reported a case of a 9-year-old male who had an extramedullary presentation of RUNX1::RUNX1T1 translocated AML. 18 The patient presented with cranial nerve palsies; however peripheral blood smears showed blasts with Auer rods. Patient underwent AML 15 Medical Research Council protocol and cranial radiotherapy and attained a 1-month disease-free survival at the time of publication of the case report.…”
Section: Discussionmentioning
confidence: 99%